School Financial Management Based on BOS Funds: A Case Study of Funding Diversification and Budget Efficiency - Nurani Nurani; Wahyu Fabriana; Undang Rosyidin (Revenue Journal: Management and Entrepreneurship, 2026)
School Financial Management Based on BOS Funds: A Case Study of Funding Diversification and Budget Efficiency